The Development of Guidance and Counseling Platform Using Google Sites-based “Friend Story” (Storytelling) Media for College Students at UIN Ar-Raniry - Tengku, Tengku Febri Irwansyah; Elviana, Elviana (IKIP Siliwangi, 2024)
English: This research aims to develop and test the feasibility of the Google Sites-based